Cortisol, cortisone, and BDNF in amniotic fluid in the second trimester of pregnancy: Effect of early life and current maternal stress and socioeconomic status - Deuschle, Michael; Hendlmeier, Ferdinand; Witt, Stephanie; Rietschel, Marcella; Gilles, Maria; Sánchez Guijo, Alberto; Fañanas, Lourdes; Hentze, Sabine; Wudy, Stefan A.; Hellweg, Rainer (Development and psychopathology, 2018)
The prenatal environment shapes the offspring's phenotype; moreover, transgenerational stress and stress during pregnancy may play a role. Brain-derived neurotrophic factor (BDNF) and glucocorticoids influence neurodevelopment during pregnancy, and there is evidence that BDNF in amniotic fluid is mainly of fetal origin, while the source of glucocorticoids is maternal. We tested the hypothesis that maternal early life stress, psychiatric diagnoses, anxiety, perceived stress, and socioeconomic status influence BDNF and glucocorticoid concentrations in amniotic fluid in the second trimester. We studied 79 pregnant women who underwent amniocentesis in the early second trimester and analyzed BDNF, cortisol, and cortisone concentrations in amniotic fluid. The endocrine data were related to maternal early life adversities (Childhood Trauma Questionaire), perceived stress (Perceived Stress Scale), anxiety, socioeconomic status (family income), and the presence of psychiatric diseases. We found BDNF in amniotic fluid to be positively related to maternal early adversity (Childhood Trauma Questionaire). Low family income (socioeconomic status) was related to high amniotic fluid glucocorticoid concentrations. Neither glucocorticoid concentrations nor hydroxy steroid dehydrogenase (HSD2) activity could be related to BDNF concentrations in amniotic fluid. Early maternal adverse events may be reflected in the fetal BDNF regulation, and it should be tested whether this relates to differences in neurodevelopment.